PENGARUH AKTIVITAS WISATA TERHADAP KUALITAS AIR DANAU TOBA DI PANTAI SIBOLAZI DESA SIMANINDO KABUPATEN SAMOSIR SUMATERA UTARA Effect of Human Activities on Water Quality of Lake Toba at Sibolazi Beach Simanindo Village, Samosir District, North Sumatera - Gracia Denata Tumanggor; Pindi Patana; Indra Lesmana (AQUACOASTMARINE, 2018)
The lake Toba is one of potential water resources for human activities such as agricultural industry development, fishery, transportation, irrigation, drinking water, tourism, and the protection of various aquatic biota. This research was conducted in June-July 2017 at Sibolazi Beach Simanindo Village, Samosir regency of North Sumatera, by analyzing the influence of tourism activity on water quality of Lake Toba and knowing the perception of visitor and manager towards Sibolazi Beach tourism. The parameters observed were Temperature, Brightness, Color, Flow Rate, pH, DO, BOD5, N, P and Total coliform. The results according to the Government Regulation No. 82 of 2001 and with the STORET rating system showed that stations 1 and 2 was classified in Class B (Moderately Polluted) with scores of -10 and -2, while station 3 was in Class A (Not Polluted) by fulfilling the quality standard class I. Visibility of visitors to Sibolazi Beach tour of 91% stated Beautiful and comfort level of 71% included in the category of Comfort and the level of visitor satisfaction of travel by 63%. Managers handle waste burning and there is no board for tourist to put the rubbish into the box.Key word : Water Quality, Lake Toba, Sibolazi Beach, Perceptions.